Continuous administration of mirabegron has advantages in inhibition of central sensitization compared with short‐term treatment cessation in a mouse model of overactive bladder. Issue 6 (12th May 2022) - Kwon, Joonbeom; Lee, Eun‐Ju; Park, Hye‐Ri; Cho, Hyun‐Jung; Jang, Ji‐Ae; Yang, Hyoungoh; An, Jihyun; Park, Donghwi; Kim, Yeon‐Joo; Hur, Kyung‐Jae; Kim, Jae‐Soo; Yoshimura, Naoki
Abstract: Aims: There is no clear pathophysiologic evidence determining how long overactive bladder (OAB) medication should be continued. We, therefore, investigated the effect of mirabegron using cessation (CES) or continuation (CON) treatment in an OAB animal model. Methods: Female C57BL/6 mice were divided into four groups ( N = 8 each): Sham, OAB, CES, and CON groups. The OAB‐like condition was induced by three times weekly intravesical instillations of KCl mixture with hyaluronidase. After the last intravesical instillation for inducing OAB, mirabegron (2 mg/kg/day) was administered in CES and CON groups for 10 and 20 days, respectively. Final experiments were carried out on 20 days from the last intravesical instillation in all groups. After cystometry, mRNA levels of bladder muscarinic, β‐adrenergic, and P2X purinergic receptors were measured to investigate bladder efferent and afferent activity. In addition, mRNA levels of CCL2 and CCR2 in L6‐S1 dorsal root ganglia (DRG) were measured to assess afferent sensitization. Immunofluorescent staining of CX3CR1, GFAP, and CCR2 in the L6 spinal cord was also conducted to investigate glial activation and central sensitization. Results: OAB mice showed bladder overactivity evidenced by decreased intercontraction interval (3.56 ± 0.51 vs. 5.76 ± 0.95 min in sham mice), increased non‐voiding contractions (0.39 ± 0.11 vs. 0.13 ± 0.07/min in sham mice), and inefficient voiding (72.1 ± 8.6% vs. 87.1 ± 9.5% in sham mice). Increased M2, M3, β2, β3, P2X2, P2X3, P2X4, and P2X7 levels in the bladder and increased CCL2 and CCR2 in DRG indicate bladder efferent and afferent hyperexcitability. In addition, CX3CR1, GFAP, and CCR2 in the L6 spinal cord were upregulated in OAB mice. However, the CON group exhibited reduced β2, β3, P2X2, P2X3, P2X4, and P2X7 levels in the bladder, reduced CCL2 and CCR2 in DRG, which are markers of afferent hyperexcitability, and reduced immunoreactivities of CX3CR1, GFAP, and CCR2 in the L6 spinal cord, which are markers of the central sensitization. Moreover, the CON group showed better improvements in nonvoiding contractions (0.16 ± 0.09 vs. 0.44 ± 0.17/min) and voiding efficiency (93.9 ± 7.4% vs. 76.5 ± 13.1%) and reductions in bladder β3 receptors and CCL2 of L6‐S1 DRG, and immunoreactivities of CX3CR1 and GFAP in the L6 spinal cord compared to the CES group. Conclusions: Continuous mirabegron treatment seems to prevent central sensitization and, thus, might be desirable for long‐term disease control of OAB.